Perlindungan Hukum Terhadap Pemilik Merek Atas Pemalsuan Merek Oleh Pelaku Usaha Melalui Transaksi Perdagangan Elektronik (E-Commerce) - Cherry Fajrini Rafli; Rani Apriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Trademarks are one of the most valuable intellectual property instruments. Trademarks could increase economic value for products that are attached to the brand, besides that trademarks could bring immaterial asset in the form of a good reputation and positive image of related products. Therefore, trademarks are recognized and given protection through Law Number 20 of 2016 on Marks and Geographical Indications. However, many trademark infringement were found in the form of trademark counterfeiting through electronic commerce transactions in order to achieve the economic value and reputation of the related brand. Therefore, the Author conducted this study in order to analyze the legal protection for trademark holder for said acts of trademark infringement in the form of trademark counterfeiting. The research method applied in this study is juridical-normative, using a literature study approach with the analytical technique used is descriptive analysis. From this study, it can be concluded that for acts of trademark infringement in the form of trademark counterfeiting through electronic commerce transactions (e-commerce) there are 2 means of legal protection, that is preventive legal protection which can be done by registering a trademark, and repressive legal protection by reporting/complaint of intellectual property infringement to the e-commerce, or through litigation by filing a civil lawsuit or criminal prosecution against the perpetrators of trademark infringement in the form of trademark counterfeit.